Comparison of properties inherent to wave plates and Fresnel rhomb - Kulish, M.R.; Virko, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Principles of functioning and technical characteristics of wave plates and
Fresnel rhomb are analyzed, and the properties of these optical elements are compared.
Main fields of application are discussed.